JOAN FONTCUBERTA'S LANDSCAPES — REMAPPING PHOTOGRAPHY AND THE TECHNOLOGICAL IMAGE. - Keller, Patricia (Journal of Spanish Cultural Studies, 2011)
An essay is presented on the remapping method of Joan Fontcuberta for landscapes, photography, and technological image. It offers the concept of landscape, in which Fontcuberta explores the intersection between photography and digital imaging. It says that Fontcuberta's Googlegrams project depicts the traditional logic of photography that immobilizes the flow of history through an arrest or capture. Moreover, the Fontcuberta's works offer persuasive cultural critiques for radical revision.